Optimalisasi Bahasa Anak Usia Dini Melalui Permainan Susun Huruf - Febriana, Ika; Silalahi, Tsalitsa Gunawan; Zahara, Siti; Pefrianti, Indah; Ismawan, Najwa Rana; Sinaga, Gloria Stefany Advenesia; Lingga, Imel Betsaida (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to optimize early childhood language development through letter-composing games. Language is a basic skill that is very important for children's development, especially at an early age. Letter arranging games are believed to help children recognize, understand and use words in a fun and interactive way. The method used in this research is the literature study method. Data was collected from various academic literature, such as journal articles, books, theses and relevant research reports. The results of the research show that through this game, children experience improvements in speaking ability, letter recognition, and the ability to put together words and sentences. This research concludes that letter arranging games are effective in optimizing early childhood language development, and can be used as a fun and educational learning method for children.